Implementation of Three Phase-Discontinuous Space Vector Modulation Using Single DSC-PWM Module - Stepan Janous; Jozef Sedlak; Michal Prazenica; Jozef Kuchta (Communications - Scientific letters of the University of Zilina, 2013)
The paper presents an implementation of a discontinuous space vector modulation of three phase inverter. The modulation is implemented in a DSC (Digital Signal Controller) using only one PWM module. Phases of the inverter work in a complementary mode. This implementation gives an assumption to use one DSC for simultaneous controlling of several three phase inverters. Furthermore, a simulation comparison of discontinuous and continuous space vector modulation is made.